A Study on the Seismic Response Characteristics of an Oblique Pile Group-Soil-Structure with Different Pile Caps - Desen Kong; Yifei Bai; Yongpo Chen; Meixu Deng (Shock and Vibration)
For the study of interaction between piles-soil-structure with different caps, the FLAC3D finite difference software was used as the research tool, and dynamic load was El Centro seismic wave. The numerical model of obliquely pile groups of the pile-soil-structure with low cap and high cap was established, respectively. The variation of pore pressure, the moment, the displacement of piles, and the displacement of pier was analyzed. The results indicate that under the action of earthquake, the distribution of pore water pressure in the soil layer increases gradually from top to bottom. The instantaneous negative value of partial soil due to shear dilation occurs at the peak of vibration acceleration. The middle area of the pile foundation in sandy soil is prone to liquefaction. In the same model, the maximum bending moment of inclined piles is greater than that of vertical piles. The vertical displacement of the vertical piles is a constant value along the depth, while the vertical displacement of the inclined piles is changed along the depth of the buried piles. In the high cap model, the horizontal displacement of the inclined piles is no longer monotonous along the burying depth, and the maximum value occurs in the sand soil layer. The vertical and horizontal displacements of the inclined piles and vertical piles in the high cap model are obviously greater than those of the low cap model. The maximum horizontal displacement of the pier of the two models occurs at the same time.